Combined physiological and transcriptome analysis revealed the response mechanism of Pogostemon cablin roots to p-hydroxybenzoic acid - Yan, Wuping; Cao, Shijia; Liu, Xiaofeng; Yao, Guanglong; Yu, Jing; Zhang, Junfeng; Bian, Tengfei; Yu, Wengang; Wu, Yougen (Frontiers in Plant Science, 2022)
Pogostemon cablin (patchouli) cultivation is challenged by serious soil sickness, of which autotoxins accumulation is a major cause. p-hydroxybenzoic acid (p-HBA) is one of the main autotoxins of patchouli. However, the molecular mechanism underlying the response of patchouli to p-HBA remains unclear. In this study, RNA-sequencing combined with physiological analysis was used to monitor the dynamic transcriptomic and physiological changes in patchouli seedlings 0, 6, 12, 24, 48, and 96 h after p-HBA treatment. p-HBA stress inhibited root biomass accumulation, induced excessive hydrogen peroxide accumulation and lipid peroxidation, and activated most antioxidant enzymes. Compared with that of the control, the osmotic adjustment substance content was elevated with treatment. Subsequently, 15,532, 8,217, 8,946, 2,489, and 5,843 differentially expressed genes (DEGs) at 6, 12, 24, 48, and 96 h after p-HBA treatment, respectively, were identified in patchouli roots. GO functional enrichment analysis showed that the DEGs were enriched mainly in plasma membrane, defense response, response to chitin, DNA-binding transcription factor activity and abscisic acid-activated signaling pathway. The upregulated genes were involved in glycolysis/gluconeogenesis, cysteine and methionine metabolism, starch and sucrose metabolism, biosynthesis of unsaturated fatty acids, and linoleic acid metabolism. Genes associated with MAPK signaling pathway-plant, plant-pathogen interaction, plant hormone signal transduction were downregulated with p-HBA treatment. These pathways are related to root browning and rotting, leading to plant death.